2020
DOI: 10.1155/2020/7929585
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Clinical Study of a Freely Removable Implant-Supported Fixed Dental Prosthesis by a Microlocking System

Abstract: This retrospective clinical study was conducted to evaluate the clinical usefulness of a freely removable microlocking implant prosthesis (MLP) that was developed to overcome the problems with conventional implant prostheses. A total of 54 patients (male: 31, female: 23) and 100 implant prostheses were included. Patients were divided into three groups such as 6-12 months, 12-18 months, and 18-24 months according to the used period after implant prosthesis delivery, and the patients in each group were recalled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Several laboratory studies, case reports, and clinical studies have suggested the possible successful clinical application of the ML system [ 26 , 27 , 28 ]. However, in a 1 year prospective clinical study, the cumulative survival rate of implants in MLF was reported to be 100%, which indicates that changing the implant prosthesis connection method would not significantly affect implant survival [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several laboratory studies, case reports, and clinical studies have suggested the possible successful clinical application of the ML system [ 26 , 27 , 28 ]. However, in a 1 year prospective clinical study, the cumulative survival rate of implants in MLF was reported to be 100%, which indicates that changing the implant prosthesis connection method would not significantly affect implant survival [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiographs were taken by using a Portable X-ray unit (Port II, Genoray, Seongnam, Korea) and measurements were obtained by using the PACS software (Digi-X, Hanjin Digi-X Co., Seoul, Korea). The means and standard deviations were calculated after scale correction based on known fixture lengths ( Figure 4 ) [ 29 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations